Pure Motor Onset and IgM-Gammopathy Occurrence in Multifocal Acquired Demyelinating Sensory and Motor Neuropathy. (5th October 2021) - Beecher, Grayson; Shelly, Shahar; Dyck, P. James B.; Mauermann, Michelle L.; Martinez-Thompson, Jennifer M.; Berini, Sarah E.; Naddaf, Elie; Shouman, Kamal; Taylor, Bruce V.; Dyck, Peter James; Engelstad, JaNean; Howe, Benjamin M.; et al.
Abstract : Background and Objectives: To longitudinally investigate patients with multifocal acquired demyelinating sensory and motor neuropathy (MADSAM), quantifying timing and location of sensory involvements in motor onset patients, along with clinicohistopathologic and electrophysiologic findings to ascertain differences in patients with and without monoclonal gammopathy of uncertain significance (MGUS). Methods: Patients with MADSAM seen at Mayo Clinic and tested for monoclonal gammopathy and ganglioside antibodies were retrospectively reviewed (January 1, 2007–December 31, 2018). Results: Of 76 patients with MADSAM, 53% had pure motor, 16% pure sensory, 30% sensorimotor, and 1% cranial nerve onsets. Motor-onset patients were initially diagnosed with multifocal motor neuropathy (MMN). MGUS occurred in 25% (89% immunoglobulin M [IgM] subtype), associating with ganglioside autoantibodies ( p < 0.001) and higher IgM titers ( p < 0.04). Median time to sensory involvements (confirmed by electrophysiology) in motor onset patients was 18 months (range 6–180). Compared to initial motor nerve involvements, subsequent sensory findings were within the same territory in 35% (14/40), outside in 20% (8/40), or both in 45% (18/40). Brachial and lumbosacral plexus MRI was abnormal in 87% (34/39) and 84% (21/25), respectively, identifying hypertrophy and increased T2 signal predominantly in brachial plexus trunks (64%), divisions (69%), and cords (69%), and intrapelvic sciatic (64%) and femoral (44%) nerves. Proximal fascicular nerve biopsies (n = 9) more frequently demonstrated onion-bulb pathology ( p = 0.001) and endoneurial inflammation ( p = 0.01) than distal biopsies (n = 17). MRI and biopsy findings were similar among patient subgroups. Initial Inflammatory Neuropathy Cause and Treatment (INCAT) disability scores were higher in patients with MGUS relative to without ( p = 0.02). Long-term treatment responsiveness by INCAT score reduction ≥1 or motor Neuropathy Impairment Score (mNIS) >8-point reduction occurred in 75% (49/65) irrespective of MGUS or motor onsets. Most required ongoing immunotherapy (86%). Patients with MGUS more commonly required dual-agent immunotherapy for stability ( p = 0.02). Discussion: Pure motor onsets are the most common MADSAM presentation. Long-term follow-up, repeat electrophysiology, and nerve pathology help distinguish motor onset MADSAM from MMN. Better long-term immunotherapy responsiveness occurs in motor onset MADSAM compared to MMN reports. Patients with MGUS commonly require dual immunotherapy. Classification of Evidence: This study provides Class II evidence that most clinical, electrophysiologic, and histopathologic findings were similar between patients with MADSAM with and without MGUS.